Occupation and Male Infertility among Selected Group of Sudanese Patients with Infertility Disorders (Global Journal of Medical Research, 2018)
Background: Occupation affect directly or indirectly the reproductive system of male and that may lead to serious complications, which may lead finally to male infertility. Justification: There is no published data about the association between occupation and fertility among Sudanese males. Objectives: To know which type of the occupations is associated with high infertility rate than the other jobs among the study group Method: Descriptive, cross sectional study, 157 participants involved in the study from different occupational environments. Result: Workers were the most affected group (29.2%) followed by shopkeepers (10.8%), drivers (10.2%), employees (8.2%), Engineers (7.6), Security officers (5.7%), teachers (3.2%), farmers (3.2%), medical (1.9%), butchers (1.2%), others (18.8%). Discussion: Occupation settings , overheated environment and work stress affect directly or indirectly in male fertility and may lead to infertility , our study agreed with that of B Baranski in points of the effects work settings and heat . Conclusion: Further studies should be done with large sample size Acknowledgement: To all persons whom participated in the study.
Keywords: occupation; male infertility; sudanese